Pengembangan Model E-Bisnis di Indonesia - Mohammad Subekti (Bina Nusantara University, 2014)
Problems in building e-business is the number of influential factors that really should be considered in the design, especially from the aspect of a relatively bad infrastructure in Indonesia. By doing appropriate design, it can at least reduce the impact due to various shortcomings that exist, it is intended that the users are able to surf comfortably and safely in a business website in cyberspace. In managing e-Business, there are business models that can be done by the businessman in the virtual world, but the e-Business models vary according to the character and culture of each region. What e-Business models are suitable to be applied in Indonesia, according to the character and culture of Indonesia, as well as the ability of the existing infrastructure will be described in this article. One solution is the utilization of social networking that is widely used, even though there are positive and negative sides of it. Then, what kinds of advantages are gained, in both for managing the site and as well as benefits for the customers